Product Innovation Factors and Selling Prices can Increase Sales Marketing at Keyzura Furniture - Suganda, Aru; Anggi Josetio Prayoga (Journal of Managiere and Business, 2024)
The furniture industry market continues to experience dynamic changes that demand product innovation and the right pricing strategy to maintain competitiveness. This article explores the role of product innovation factors and selling price policies in improving sales performance at Mebel Keyzura. The research adopts descriptive and case study analysis methods, combining primary data from consumer surveys and secondary data related to furniture industry trends. The results show that product innovation that prioritizes ergonomic design, environmentally friendly materials, and deep technology integration provides a competitive advantage for keyzura furniture. In addition, pricing that takes into account the added value of innovation, market positioning, as well as consumer sensitivity to price, helps influence purchasing decisions. Flexible pricing strategies, such as product bundling, planned discounts, and offers for loyal customers, are proven to increase product appeal and sales. Pasar industri furnitur terus mengalami perubahan dinamis yang menuntut inovasi produk dan strategi harga yang tepat untuk menjaga daya saing. Artikel ini mengeksplorasi peran faktor inovasi produk dan kebijakan harga jual dalam meningkatkan kinerja penjualan di Mebel Keyzura. Penelitian ini menggunakan metode analisis deskriptif dan studi kasus, yang menggabungkan data primer dari survei konsumen dan data sekunder terkait tren industri furnitur. Hasilnya menunjukkan bahwa inovasi produk yang mengedepankan desain ergonomis, material ramah lingkungan, dan integrasi teknologi yang mendalam memberikan keunggulan kompetitif pada furnitur keyzura. Selain itu, penetapan harga yang mempertimbangkan nilai tambah inovasi, positioning pasar, serta sensitivitas konsumen terhadap harga, turut mempengaruhi keputusan pembelian. Strategi penetapan harga yang fleksibel, seperti bundling produk, diskon terencana, dan penawaran untuk pelanggan setia, terbukti meningkatkan daya tarik produk dan penjualan.